2006
DOI: 10.1136/qshc.2005.016808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of computerisation on the quality and safety of chemotherapy prescription

Abstract: Background: Chemotherapy is prescribed according to protocols of several cycles. These protocols include not only therapeutic agents but also adjuvant solvents and inherent supportive care measures. Multiple errors can occur during the prescription, the transmission of documents and the drug delivery processes, and lead to potentially serious consequences. Objective: To assess the effect of a computerised physician order entry (CPOE) system on the number of errors in prescription recorded by the centralised ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 24 publications
2
86
1
1
Order By: Relevance
“…In total, seven unique quantitative and two unique qualitative papers met the eligibility criteria for the systematic review ( Figure 1). The research designs described in the quantitative studies included 2-arm trials [17][18][19][20] and pre-post study designs [21][22][23] . The subsection that follows describes the outcomes of the review as they relate to the original research questions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, seven unique quantitative and two unique qualitative papers met the eligibility criteria for the systematic review ( Figure 1). The research designs described in the quantitative studies included 2-arm trials [17][18][19][20] and pre-post study designs [21][22][23] . The subsection that follows describes the outcomes of the review as they relate to the original research questions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The results of the present systematic review clearly demonstrated the paucity of oncologyspecific cpoe literature, but the studies cited here are consistent with the existing systematic reviews describing the benefits of cpoe systems 14,27 and the unanticipated outcomes 28 . The few studies included in this review demonstrate that cpoe in the oncology setting does contribute to a decline in the incidence of medication errors 17,18,[21][22][23] , as it does, in some instances, to the potential for increased errors 18,19,21,23 . The cpoe system, clinical decision supports, and associated interface elements must be carefully designed to optimize the benefits of st cpoe systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computerized physician order entry (cpoe) has been shown to significantly improve chemotherapy safety by reducing the number of prescribing errors [1][2][3][4][5][6][7] . Since the early 2000s, research has established a knowledge base for successful cpoe implementation and ongoing use.…”
Section: Introductionmentioning
confidence: 99%